Cumplimiento esquema de vacunación en menores de 2 años, Centro De Desarrollo Infantil “Estrellitas De Luz” - San Gabriel - Bastidas Itás, Sandra Esthefania (2024)
The lack of adequate vaccination exposes children to completely preventable diseases, which implies serious consequences resulting in even fatal results; this situation not only compromises the individual health of children but also compromises the collective immunity, thus increasing therisks of epidemics or outbreaks. To this purpose, the objective of this research was addressed to develop an educational plan to improve the accomplishment of the national vaccination schemes among children under 2 years, in the Child Development Center “Estrellitas de Luz”, located in the city of San Gabriel. The methodology used was based on a quantitative paradigm, supported by diverse types of research such bibliographic, action, field and descriptive. The instrument for data collection wasthe questionnaire, which was applied to the parents or caregivers of the childrenwho attend the abovementioned center. The main results highlighted that 44% of the population had only completed the primary education, suggesting that the lack of completed education can influence the comprehension of the importance of the logistics of the vaccination plans; 35% of the population claimed to work part-time, which reflects economic restrictionsso that to follow orafford the vaccination schemes; this is especially true when 58% of the population live in rural areas, where the access to these centers is more limited, similarly 42% indicated that they never receive any type of information regarding the vaccination schemes, which emphasizes a clear lackof communication between the health services centers and the communities they attend